Analysis of the wrinkle geometry of the woven fabrics during uniaxial bias extension test using Ricker wavelet algorithm. (February 2021) - Moezzi, Meysam; Haji-Badali, Ali; Barez, Fred
Abstract: Out-of-plane wrinkling has a significant influence on the woven fabric behavior during the shear testing. This study aimed to introduce a new methodology combining non-destructive characterization and numerical analysis techniques for the automatic creation of a number of models having controlled wrinkle geometry and predict the new ones. First, 3D geometrical parameters of the fabric deformation at different crosshead displacements were measured. Then, the Ricker Wavelet equation was selected according to wrinkle topology and the function parameter was estimated. The correlation of the geometrical measured and function estimated parameters with the crosshead displacement values were obtained. The correlated function was used to predict the wrinkle geometry in the new crosshead displacement. The validation and accuracy of the predicted wrinkle geometry was confirmed by the image processing method. Finally, the effect of wrinkle maximum depth and shear angle on Poisson's ratio showed a decrease due to an increase of them.